VIVÊNCIAS DE PAIS DE CRIANÇAS NASCIDAS COM MICROCEFALIA NO CONTEXTO DA EPIDEMIA DO VÍRUS ZIKA. - OLIVEIRA, Poliana Soares de (2019)
INTRODUCTION: In Brazil, in 2015, there was a microcephaly epidemic that was associated with maternal Zika virus infection during pregnancy. The news about these cases of microcephaly distressed and changed the imagination of fathers and mothers regarding the expectations for the arrival of the child. Therefore, the objective of this research was to analyze the experiences of parents of children born with microcephaly in the context of the Zika virus epidemic. METHOD: This is a qualitative study conducted at the State Reference Center on Neurodevelopment, Care and Rehabilitation of Children (NINAR), in São Luís, from April / 2017 to February / 2018. The parents of children with microcephaly participated in the study. Data collection techniques were structured and semi-structured interviews conducted with 3 couples, 16 mothers and one great-grandmother, totaling 20 interviews. The sample was defined in the field by the saturation criterion and thematic content analysis was performed. RESULTS: For 18 respondents, the form of communication was considered inappropriate and traumatic, sometimes linked to the meaning of “end of life” and dissociated from guidance on ways to cope with the situation and take care of the child. The diagnosis of microcephaly was given by doctors in 15 of the 20 cases and in three cases: by a nurse, by the mother-in-law (who knew by the doctor) and by an official of the health department. The other two were not diagnosed: one couple learned of microcephaly from the live birth statement (DNV) and another associated the characteristics of their child with information in the media. The main situations found were omission of diagnosis, inadequate communication of diagnosis and anticipation of prognosis. There were several ways in which mothers felt and responded to the news of having a child with microcephaly: shock, surprise, despair, sadness, fear, anxiety, anger, disappointment, seeking for more information, religious explanations, blaming, acceptance and denial. Expectations involved concerns mainly about the fear of death, the motor development of the child and their dependence on care related to early experiences. Regarding the search for care in the health sectors, the results showed disorientation and uncertainties. The most sought after sector was the professional, followed by the informal and popular. The information conveyed in the media and social networks, which are part of the informal sector, contributed to clarify the meaning of the disease and assist in the search for treatment. FINAL CONSIDERATIONS: The ways of communicating the diagnosis of microcephaly to the family members influenced the ways of acceptance and coping with the situation. The reactions and feelings evidenced the elaboration of a grieving process, facing the birth of a child different from what they expected and planned. Care in the health care network was marked by pilgrimage, especially to access the system. Faced with a new and emergency situation, the path taken between diagnosis and treatment was arduous.